Pengaruh Lokasi Dan Fitur Mobile Banking Terhadap Minat Masyarakat Dalam Melakukan Transaksi Bank Syariah Pada Desa Sambirejo Timur Kabupaten Deli Serdang - Muhammad Raihan Nul Ihsan; Dahrani Dahrani (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research is to measure the extent to which location ank moile aki feature influence people’s interest in carrying out sharia banking transactions. This research uses data obtained from distributing questionnaires to the community, the research method is quantitative using the SPSS analysis measuring tool. Yhe result of this research show that there is a simultaneous influence between location (X1) dan mobile banking features (X2) on people’s interest in carrying out Islamic bank transactions (Y), the result of which have a positive effect of 85,6%